Capacity Building in Risk Prevention and Mitigation for Micro and Small Enterprises: Evidence from a Community Engagement Program - Richy Wijaya; Abubakar Arief; Rayi Retno Dwi Asih; Rizky Ramzi Rahmawan; Dendy Mohammad Prabowo (CV. AFDIFAL MAJU BERKAH, 2026)
Micro and small enterprises (MSEs play a critical role in Indonesia’s economic resilience, yet they remain highly vulnerable to operational, financial, and market uncertainties due to limited risk management capabilities. This study reports the results of a community service–based training program conducted at the Cordova Entrepreneurship School, Tangerang, which aimed to strengthen participants’ capacity to identify, analyze, and mitigate business risks through preventive strategies and the Bow Tie risk management method. The program involved ten student participants (five male and five female) and employed a pretest–posttest design using structured questionnaires administered via Google Forms. The training materials covered fundamental concepts of uncertainty, types of business risks, the risk management process, preventive measures, and practical application of the Bow Tie method. Quantitative analysis of pre-test and post-test scores indicates a consistent improvement in participants’ understanding of risk management concepts, reflecting the effectiveness of experiential and structured risk-based learning. The findings align with prior studies emphasize the positive relationship between enterprise risk management practices and microbusiness performance, adaptability, and sustainability. Beyond individual learning outcomes, the program contributed to institutional objectives by integrating community engagement with teaching and student development under the Merdeka Belajar Kampus Merdeka (MBKM) framework. Overall, this study demonstrates that targeted, context-sensitive risk management training can significantly enhance risk awareness and managerial readiness among aspiring micro-entrepreneurs, thereby supporting long-term business resilience and community empowerment